Optimisation of the alcoholic fermentation of aqueous jerivá pulp extract (Acta Scientiarum. Technology, 2014)
The objective of this research is to determinate the optimum conditions for the alcoholic fermentation process of aqueous jerivá pulp extract using the response surface methodology and simplex optimisation technique. The incomplete factorial design 3Â³ was applied with the yeast extract, NH4H2PO4 and yeast as the independent variables and the alcohol production yield as the response. The regression analysis indicated that the model is predictive, and the simplex optimisation generated a formulation containing 0.35 g L-1 yeast extract, 6.33 g L-1 yeast and 0.30 g L-1 NH4H2PO4 for an optimum yield of 85.40% ethanol. To validate the predictive equation, the experiment was carried out in triplicate under optimum conditions, and an average yield of 87.15% was obtained. According to a t-test, no significant difference was observed (on the order of 5%) between the average value obtained and the value indicated by the simplex optimisation technique.Â